2023
DOI: 10.1007/s00464-023-10095-w
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical and oncological outcomes of laparoscopic right hemicolectomy (D3 + CME) for colon cancer: A prospective single-center cohort study

Abstract: Background Complete mesocolic excision (CME) or D3 lymphadenectomy led to survival benefits for locally advanced right colon cancer, but with vague definitions in anatomy and debated surgical hazard in clinic. Aiming to achieve a precise definition of it in anatomy, we proposed laparoscopic right hemicolectomy (D3 + CME) as a novel procedure for colon cancer. However, the surgical and oncological results of this procedure in clinic were uncertain. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The mean number of 15.9 ± 7.4 LNs were retrieved from artery-oriented D3 area in the cadaveric study (3). In the recent prospective single-center cohort study, conducted by Xiaolin et al, it was shown that the combination of the possible preservation of fascial integrity and central vascular ligation with proper landmarks (CME + D3) demonstrated improved cumulative survival outcomes, both disease-free and overall-survival rates (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean number of 15.9 ± 7.4 LNs were retrieved from artery-oriented D3 area in the cadaveric study (3). In the recent prospective single-center cohort study, conducted by Xiaolin et al, it was shown that the combination of the possible preservation of fascial integrity and central vascular ligation with proper landmarks (CME + D3) demonstrated improved cumulative survival outcomes, both disease-free and overall-survival rates (4).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are two commonly accepted standards to D3LND: the rst approach considers SMV and its trunk as the main anatomical landmark, which should be dissected till the Henle's trunk (1,2). The second approach considers superior mesenteric artery at its left lateral side to include the watershed area of lymph node spread at the root of mesocolon (3)(4)(5). Thus, thorough understanding of spatial vascular anatomy is important to follow the landmarks of lymph dissection.…”
Section: Introductionmentioning
confidence: 99%